Casting of film-cooling holes for single-crystal blades - Kai Miao; Wenliang Xu; Fusheng Cao; Yang Ran; Zhongliang Lu; Fu Wang; Dichen Li (Journal of Materials Research and Technology, 2023)
The flawless formation of film-cooling holes (FCHs) is critical for manufacturing single-crystal blade. Presently, high-energy beam drilling is mostly used to process gas film holes, which introduces the limitations of complex hole structures that are difficult to form and processing thermal defects that are difficult to eliminate. This study demonstrates an approach to form FCHs using casting, where an indirect additive manufacturing technology using a core/shell integral ceramic mold is applied for casting. Cylindrical 0.4, 0.8, and 4.0 mm-diameters hole are cast. The influence of fine ceramic cores on the microstructure of single-crystal blades during directional solidification is investigated using simulations and experiments. The fine ceramic cores of the FCHs affect the growth morphology of dendrites around the hole, which is determined by the hole diameter, primary dendrite spacing, and local temperature filed. Owing to the thermal conductivity difference between the alloy and ceramic, the local temperature filed around the holes changes abruptly, leading to the formation of shrinkage porosity and cavities. Furthermore, the process window for the casting of FCHs is determined using the longitudinal temperature gradient (GZ) and solidification rate (VZ). The proposed approach is of practical significance for the defect-free casting of tiny structures in single-crystal blades.